PENGEMBANGAN MODUL IPA BERBASIS SAINTIFIK PADA TEMA POLUSI UDARA UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KETERAMPILAN PROSES SAINS (KPS) SISWA DI SMP/MTs KELAS VIII - Ervian Arif Muhafid; Suparmi Suparmi; Widha Sunarno (Magister Pendidikan Sains Universitas Sebelas Maret, 2017)
The purpose of this study was to determine the characteristics, the feasibility, the increase of motivation to learn and students’ science process skills through scientific modules in based of scientific. The methode used in this research is R&D (Research and Development) in model of 4-D (define, desain, develop, and desseminate). The subject of this research is class 8th of Junior High School Satu Atap Ayah. The trial begins with a pretest and after learning using module, it ends with posttest. The module is then propagated to the MGMP teachers to get feedback. The results of this study shows that the characteristic of module which is developed using 4-D model and integrating learning motivation including attention, relevant, confidence, satisfaction and science process skills include observing, asking, gathering information, processing information, and communicating. The results showed that the average of expert assessment to the product developed is 2.51 so the module declared as feasible by experts. Observation of learning motivation showed 2.87 (poor) increased be 3.17 (good) and there are significant difference between before and after using the module on aspects of relevance, confidence and satisfaction, but not significant in aspects of attention. The increase is declared with n-gain score and showed the score 0.3 (moderate). Learning motivation questionnaire obtained an average score of student motivation 3.19 (good). The observation of science process skills was 2.96 (unfavorable) increased to 4.08 (good) and there are a significant difference between before and after using the modules on all aspects of the science process skills. The increase is expressed with n-gain score which shown 0.55 (moderate). Questionnaire of science process skills was shown the students’ science process skills average 3.36 (good). The result of stages of deployment, overall MGMP teacher gave a good response.